2018
DOI: 10.1007/s11604-018-0728-1
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and images of radiation-induced hepatitis: a review article

Abstract: Recent advances in highly conformal radiotherapies greatly extend the indications for radiotherapy of liver tumors. However, because of poor tolerance to hepatic radiation, estimation of the intensity of irradiation of the liver is important, particularly for a cirrhotic liver. Knowledge of radiation-induced hepatitis is important for understanding how to optimize hepatic radiation therapy. Pathological changes of the irradiated liver, which include perivenular fibrosis, sinusoidal obstruction, and damage to K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 57 publications
(84 reference statements)
1
36
0
Order By: Relevance
“…17 The irradiated parenchyma does not take up gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) and superparamagnetic iron oxide, which can cause difficulty in distinguishing PBT-treated HCCs from the surrounding irradiated parenchyma. 18,19 Thus, dynamic CT or dynamic MRI scans using extracellular contrast agents are suitable for the assessment of tumor contrast enhancement, because they can more accurately distinguish treated HCC from irradiated parenchyma.…”
mentioning
confidence: 99%
“…17 The irradiated parenchyma does not take up gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA) and superparamagnetic iron oxide, which can cause difficulty in distinguishing PBT-treated HCCs from the surrounding irradiated parenchyma. 18,19 Thus, dynamic CT or dynamic MRI scans using extracellular contrast agents are suitable for the assessment of tumor contrast enhancement, because they can more accurately distinguish treated HCC from irradiated parenchyma.…”
mentioning
confidence: 99%
“…During angiography-assisted CT, irradiated parenchyma exhibits decreased attenuation on CT arterial portography and increased attenuation on CT arteriography, which is the result of an arterial-predominant blood supply to the irradiated parenchyma (caused by radiation-induced venoocclusive disease) [11–13]. Prolonged enhancement of the irradiated parenchyma is related to contrast agent retention in the fibrous tissue [14]. Furthermore, a previous study demonstrated that the earliest disappearance of radiation-induced hepatic injury on imaging was observed 42 months after the PBT [11–13], which suggests that the irradiated parenchyma might have diminished arterial supply that persists long after the PBT treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While exposed to radiation due to a nuclear accident or as an intended treatment for cancer, as a radiosensitive organ, the liver may suffer from radiation-induced liver injury (RILI), resulting in hepatitis, fibrosis, cirrhosis, and cancer. Typical pathological appearances of RILI in humans are perivenular fibrosis, sinusoidal obstruction, and damage to Kupffer cells (KCs) and hepatocytes [ 8 ]. The severity of RILI depends upon the nature of the radiation, the total exposure dose, the dose rate, and the physical area of exposure [ 3 ].…”
Section: Radiationmentioning
confidence: 99%